PENCUCIAN BERTINGKAT GLUKOMANAN dari UMBI PORANG (Amorphophallus oncophyllus Pr.) dengan MENGGUNAKAN ETANOL BERTINGKAT sebagai PELARUT - Sudarsono, Agustina Putri Pitarisa (Jurnal Farmasi & Sains Indonesia, 2023)
Porang tubers (Amorphophallus oncophyllus Prain) contain more glucomannan than several types of Amorphophallus. In Indonesia, this plant is not widely cultivated and only grows wild in the forest. The glucomannan content of the oncophyllus type is quite high, namely 55% compared to the konjac glucomannan type, which is 64%. This research aims to carry out graded washing of glucomanan using etanol as a solvent. The extraction of glucomannan from porang tubers starts from the process of selecting the tubers, washing, drying to extraction by washing the porang flour using graded concentrations of ethanol, 50% and 80% each for four washings, which are then characterized, such as organoleptic, water content, particle size and glucomannan content. From this research, it can be concluded that purifying glucomannan by washing in stages using 50% and 80% ethanol repeatedly, it can be seen that this purification process is able to reduce the number of impurities contained in the flour.